2022
DOI: 10.1161/hypertensionaha.121.18748
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Blood Pressure and the Risk for Early Kidney Damage in Young Adulthood

Abstract: Background: Recent guidelines classified blood pressure above 130/80 mm Hg as hypertension. However, outcome data were lacking. Objective: To determine the association between blood pressure in adolescence and the risk for early kidney damage in young adulthood. Methods: In this nationwide cohort study, we included 629 168 adolescents aged 16 to 20 who underwent medical examinations before man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…A sensitivity analysis limited to those with abnormally high BMI yielded similar results. These observations corroborate previous studies of this cohort that found associations of adolescent hypertension with other metabolic sequela such as early- 8 and end-stage kidney disease, 7 cardiovascular mortality, 9 and type 2 diabetes. 6 As our study is observational in nature, we cannot infer explicit causality.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A sensitivity analysis limited to those with abnormally high BMI yielded similar results. These observations corroborate previous studies of this cohort that found associations of adolescent hypertension with other metabolic sequela such as early- 8 and end-stage kidney disease, 7 cardiovascular mortality, 9 and type 2 diabetes. 6 As our study is observational in nature, we cannot infer explicit causality.…”
Section: Discussionsupporting
confidence: 92%
“…24 Our study suggests neurological sequela of established late-adolescent hypertension, in the form of stroke in young adulthood. This observation adds to the cumulative evidence of the potentially harmful effects of adolescent hypertension, 3,6–8 even when controlling for such central risk factors as adolescent BMI and diabetes during adult life. While stroke is less common in younger than older adults, the effects are more deleterious in terms of recurrence, disability, and death rates; and the economic impact is greater.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…As described in an earlier study, 22 we intentionally disregarded incidences of CKD that may be attributed to causes other than BMI. First, we focused on albuminuria, an early stage of CKD, as the outcome and excluded incidences in which the initial presentation included a pronounced reduction in eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…46 Effects of childhood BP on the microvasculature is less well described with no difference in microalbuminuria between normotensive and hypertensive adolescents found, 45,47 although 20% of children with primary hypertension (mean age, 16.5 years) had a random urine albumin to creatinine ratio of >3.2 mg/mmol creatinine in a retrospective chart review. 48 In a study of Israeli conscriptees (N=589 702; age, 16-20 years), 0.3% of adolescents with BP ≥130/80 mm Hg developed early kidney damage after 15.1 years, 49 and adolescent BP in this cohort has also been related to adult end-stage renal disease 50 and type 2 diabetes. 51 Danish studies of retinopathy in adolescents (16-17 years old) found a relationship between BP and retinal arteriolar wall-to-lumen ratio but only in girls.…”
Section: Relation Of Child Bp To Subclinical Cardiovascular Diseasementioning
confidence: 94%